Multilayer coil component

The laminated coil component design addresses the issue of cracking during mounting by optimizing the gap ratios between the coil and the mounting surface, resulting in improved stress resistance and reliability.

JP2025053983APending Publication Date: 2025-04-07TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163134
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Laminated coil components are prone to cracking during mounting due to stress applied to the mounting surface, which can lead to distortion and failure.

Method used

The laminated coil component design includes a specific gap ratio between the coil and the mounting surface, with the first gap in the Z-axis direction being 12 to 30% of the body's size in that direction, and the second gap in the X-axis direction being smaller, with a ratio of 1.2 to 6.0 times the first gap, to create a distance that suppresses cracks.

Benefits of technology

This design effectively suppresses cracks caused by stress during mounting by maintaining a sufficient distance between the mounting surface and the coil, thereby enhancing the reliability and durability of the laminated coil components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025053983000001_ABST
    Figure 2025053983000001_ABST
Patent Text Reader

Abstract

To provide a multilayer coil component capable of suppressing cracking caused by a stress during mounting.SOLUTION: On a cross section in a view in a Y-axis direction, with respect to a size of an element assembly 2 in a Z-axis direction, a ratio of a first gap G1 in the Z-axis direction between a coil 10 and a mounting face MF is 12 to 30%. In such a case, in the element assembly 2, between the mounting face MF which is easy to be distorted by a stress and the coil 10, a distance for suppressing cracking can be secured. Thus, the cracking caused by the stress during mounting can be suppressed.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated coil component. [Background technology]

[0002] There is known a laminated coil component including an element body and a coil disposed inside the element body (for example, Patent Document 1). In Patent Document 1, the coil has a coil axis extending in a predetermined direction. When viewed from the direction in which the coil axis extends, the coil has a rectangular shape. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-060049 A Summary of the Invention [Problem to be solved by the invention]

[0004] The laminated coil component having the above-mentioned configuration is mounted on a mounting board in an arrangement in which the coil axis extends along the mounting board. The laminated coil component is mounted with one side surface of the element body serving as a mounting surface facing the board. When the laminated coil component is mounted on the mounting board, stress is applied to the mounting surface side, which may cause cracks to occur in the element body.

[0005] An object of one aspect of the present invention is to provide a laminated coil component that can suppress cracks caused by stress during mounting. [Means for solving the problem]

[0006] The laminated coil component according to the present invention comprises an element body having a pair of first side surfaces facing each other in a first direction and a pair of second side surfaces facing each other in a second direction perpendicular to the first direction, and a coil disposed inside the element body and having a coil axis extending in a third direction perpendicular to the first and second directions, one of the pair of first side surfaces being a mounting surface, and in a cross section viewed from the third direction, the ratio of a first gap in the first direction between the coil and the mounting surface to the size of the element body in the first direction is 12 to 30%.

[0007] This laminated coil component is disposed inside an element body and includes a coil whose coil axis extends in a third direction perpendicular to the first direction and the second direction. One of a pair of first side surfaces facing each other in the first direction is a mounting surface. Therefore, the laminated coil component is mounted in such a manner that the coil axis extends along the surface of a mounting board. At this time, stress is applied to the mounting surface of the laminated coil component due to the influence of the expansion and contraction of the conductor layer of the mounting board. In contrast, in a cross section viewed from the third direction, the ratio of the first gap in the first direction between the coil and the mounting surface to the size of the element body in the first direction is 12 to 30%. In this case, a distance for suppressing cracks can be secured between the mounting surface of the element body, which is easily distorted by stress, and the coil. As described above, cracks due to stress during mounting can be suppressed.

[0008] In a cross section viewed from the third direction, the first gap may be larger than the second gap in the second direction between the coil and the second side surface. In this case, a distance for suppressing cracks can be secured between the mounting surface of the element body, which is susceptible to distortion due to stress, and the coil.

[0009] The first gap may be 1.2 to 6.0 times the second gap, in which case a distance sufficient to prevent cracks can be secured between the coil and the mounting surface of the element body that is susceptible to distortion due to stress.

[0010] In the first region between the mounting surface and the coil in the element body, a surface region constituting the mounting surface and an internal region inside the surface region may be formed, and the surface region may have a larger average crystal grain size than the internal region. In this case, the surface region having a larger average crystal grain size can suppress the occurrence of cracks on the mounting surface. On the other hand, even if cracks occur on the mounting surface, the internal region having a smaller average crystal grain size and pores can suppress the progression of the cracks to the inside.

[0011] The surface region may be 2 to 25% of the first region. In this case, a good balance can be achieved between the effect of suppressing the occurrence of cracks on the mounting surface in the surface region and the effect of suppressing the progression of cracks in the internal region.

[0012] A laminated coil component according to the present invention comprises: an element body having a pair of first side surfaces opposing each other in a first direction and a pair of second side surfaces opposing each other in a second direction perpendicular to the first direction; and a coil disposed inside the element body and having a coil axis extending in a third direction perpendicular to the first and second directions, one of the pair of first side surfaces being a mounting surface; and in a cross section viewed from the third direction, a first gap in the first direction between the coil and the mounting surface may be larger than a second gap in the second direction between the coil and the second side surfaces.

[0013] The laminated coil component includes a coil disposed inside an element body, the coil axis of which extends in a third direction perpendicular to the first direction and the second direction. One of a pair of first side surfaces facing each other in the first direction is a mounting surface. Therefore, the laminated coil component is mounted in such a manner that the coil axis extends along the surface of a mounting board. At this time, stress is applied to the mounting surface of the laminated coil component due to the effects of expansion and contraction of the conductor layer of the mounting board. In contrast, in a cross section viewed from the third direction, a first gap in the first direction between the coil and the mounting surface may be larger than a second gap in the second direction between the coil and the second side surface. In this case, a distance for suppressing cracks can be secured between the mounting surface of the element body, which is easily distorted by stress, and the coil. As described above, cracks due to stress during mounting can be suppressed.

[0014] The first gap may be 1.2 to 6.0 times the second gap, in which case a distance sufficient to prevent cracks can be secured between the coil and the mounting surface of the element body that is susceptible to distortion due to stress. Effect of the Invention

[0015] According to the present invention, it is possible to suppress cracks caused by stress during mounting. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a perspective view showing a laminated coil component according to an embodiment. [Diagram 2] FIG. 2 is an exploded perspective view showing a layer structure of the laminated coil component shown in FIG. [Diagram 3] 1 is a cross-sectional view of a mounting structure when a laminated coil component is mounted on a mounting board. [Figure 4] FIG. 4(a) is a cross-sectional view taken along line IVa-IVa shown in FIG. 3, and FIG. 4(b) is a cross-sectional view of a laminated coil component according to a comparative example. [Diagram 5] FIG. 11 is an enlarged cross-sectional view of the vicinity of the mounting surface as viewed from the Y-axis direction. [Figure 6]1A to 1C are diagrams for explaining the principle by which cracks may occur when mounting a laminated coil component. [Figure 7] This is a photograph of the first area. [Figure 8] 13 is a graph showing experimental results. [Figure 9] FIG. 11 is a cross-sectional view showing a laminated coil component according to a modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the description of the drawings, the same or corresponding elements are designated by the same reference numerals, and duplicated explanations will be omitted.

[0018] Fig. 1 is a perspective view showing a laminated coil component according to an embodiment. Fig. 2 is an exploded perspective view showing a layer structure of the laminated coil component shown in Fig. 1. Fig. 3 is a cross-sectional view of a mounting structure when the laminated coil component is mounted on a mounting board.

[0019] As shown in FIG. 1, the laminated coil component 1 includes an element body 2 having a substantially rectangular parallelepiped shape and a pair of external electrodes 4, 5 disposed at both ends of the element body 2. The element body 2 has, as its outer surface, a pair of end faces 2a, 2b facing each other, and four side faces 2c, 2d, 2e, 2f extending along the facing direction of the pair of end faces 2a, 2b so as to connect the pair of end faces 2a, 2b. Here, the direction in which the end faces 2a, 2b face each other is defined as the Y-axis direction (third direction). The direction in which the side faces 2c, 2d face each other is defined as the Z-axis direction (first direction). The direction in which the side faces 2e, 2f face each other is defined as the X-axis direction (second direction). The X-axis direction is a direction perpendicular to the Z-axis direction. The Y-axis direction is a direction opposite to the X-axis direction and the Z-axis direction. The end face 2a is disposed on the positive side of the Y-axis direction, and the end face 2b is disposed on the negative side. Side 2c is located on the positive side of the Z axis direction, and side 2d is located on the negative side. Side 2e is located on the positive side of the X axis direction, and side 2f is located on the negative side.

[0020] As shown in Fig. 2, the element body 2 is formed by stacking a plurality of insulator layers 11. Each insulator layer 11 has a rectangular shape (rectangular shape in this embodiment) and has four sides 11c, 11d, 11e, and 11f that define the side surfaces 2c, 2d, 2e, and 2f. Each insulator layer 11 is an insulator having electrical insulation properties, and is made of a sintered body of an insulator green sheet. In the actual element body 2, each insulator layer 11 is integrated to such an extent that the boundaries between them are not visible.

[0021] The insulating layer 11 may be made of ferrite (for example, Ni-Cu-Zn ferrite, Ni-Cu-Zn-Mg ferrite, Cu-Zn ferrite, or Ni-Cu ferrite).

[0022] The size of the element body 2 in the Z-axis direction is defined as dimension L1. Dimension L1 is the distance between the side surfaces 2c and 2d in the Z-axis direction. Dimension L2 is the size of the element body 2 in the X-axis direction. Dimension L2 is the distance between the side surfaces 2e and 2f in the X-axis direction. Dimension L3 is the size of the element body 2 in the Y-axis direction (see FIG. 3). Dimension L3 is the distance between the end faces 2a and 2b in the Y-axis direction. Dimension L1 may be 200 μm or more, or 250 μm or more. Dimension L1 may be 450 μm or less, or 300 μm or less. Dimension L2 may be 120 μm or more, or 170 μm or more. Dimension L2 may be 320 μm or less, or 210 μm or less. Dimension L3 may be 250 μm or more, or 340 μm or more. Dimension L3 may be 600 μm or less, or 380 μm or less. However, each dimension is not limited to these ranges.

[0023] The external electrode 4 is formed so as to cover the entire one end face 2a and parts of the four side faces 2c, 2d, 2e, 2f. The external electrode 5 is formed so as to cover the entire other end face 2b and parts of the four side faces 2c, 2d, 2e, 2f. The stacking direction of the multiple insulator layers 11 coincides with the opposing direction of the pair of end faces 2a, 2b. Therefore, the pair of external electrodes 4, 5 are respectively disposed at both ends of the element body 2 in the stacking direction of the multiple insulator layers 11. The external electrode 4 is disposed on the positive side in the Y-axis direction. The external electrode 5 is disposed on the negative side in the Y-axis direction.

[0024] Each of the external electrodes 4, 5 is formed by attaching a conductive paste mainly composed of copper, silver, gold, nickel, chromium, etc. to the outer surface of the element body 2, baking the paste, and then electroplating it. Cu, Ni, Sn, etc. can be used for the electroplating. The conductive paste is applied by, for example, a dipping method, a printing method, or a transfer method. The plating process is, for example, electrolytic plating or electroless plating. This plating process forms a plating layer on the outer surface of the conductive paste.

[0025] As shown in FIG. 2, the laminated coil component 1 includes a plurality of coil patterns 12 and a connection portion 13. The connection portion 13 includes a lead conductor 14 and a connection conductor 15. The plurality of coil patterns 12, the lead conductor 14, and the connection conductor 15 are arranged in the stacking direction of the insulating layers 11 in the element body 2. Each of the coil patterns 12, the lead conductor 14, and the connection conductor 15 includes a conductive material such as copper, silver, gold, nickel, palladium, or chromium. Each of the coil patterns 12, the lead conductor 14, and the connection conductor 15 is configured as a sintered body of a conductive paste including the conductive material. The conductor patterns that become the conductors 12, 14, and 15 are formed by screen-printing a conductive paste using a screen printing plate in which openings corresponding to the conductor patterns are formed.

[0026] Each of the conductor patterns 21 forming the coil pattern 12 is formed in a substantially U-shape. A substantially circular pad portion 23 corresponding to the through-hole conductor 22 is formed on one end and the other end of the conductor pattern 21. The conductor patterns 21 are connected in series via the through-hole conductors 22 with a phase shift of 90 degrees, forming a coil 10 having a coil axis L (see FIG. 3) that is a central axis extending along the lamination direction. The coil axis L of the coil 10 extends in the Y-axis direction. The number of turns of the coil 10 is not particularly limited.

[0027] The conductor pattern 24 forming the lead conductor 14 is composed of a substantially circular pad portion (pad conductor) 26 corresponding to the through-hole conductor 25. In other words, the lead conductor 14 is composed of the through-hole conductor 25 and the pad portion 26 provided integrally with the through-hole conductor 25. The outer end of the lead conductor 14 is exposed at the end faces 2a, 2b of the element body 2 in the stacking direction, and is connected to the external electrodes 4, 5. The lead conductor 14 is disposed in the center of the insulator layer 11.

[0028] Conductive pattern 27 forming connecting conductor 15 is formed in a straight line connecting a position corresponding to one pad portion 23 of coil pattern 12 and a position corresponding to pad portion 26 of lead conductor 14. At one end of conductor pattern 27, substantially circular pad portion 28 corresponding to through-hole conductor 25 is formed coaxially and substantially the same shape as pad portion 26 of lead conductor 14, and at the other end of conductor pattern 27, substantially circular pad portion 29 corresponding to through-hole conductor 22 is formed coaxially and substantially the same shape as pad portion 23 of coil pattern 12. As shown in FIG. 2, one end of conductor pattern 27 is connected to the other end of lead conductor 14 via through-hole conductor 25, and the other end of conductor pattern 27 is connected to the end of coil pattern 12 via through-hole conductor 22.

[0029] As shown in FIG. 3, the laminated coil component 1 is mounted on a mounting board 100. The mounting board 100 includes a board 101, conductor layers 102 and 103, and resists 104 and 105. The board 101 is a flat plate-like material that serves as a base member of the mounting board 100. The conductor layers 102 and 103 are formed on the surface of the board 101 using a conductive material. The conductor layers 102 and 103 are spaced apart from each other in the Y-axis direction. The resists 104 and 105 are insulating layers that cover the surfaces of the conductor layers 102 and 103. The resists 104 and 105 expose the conductor layers 102 and 103. The laminated coil component 1 is mounted on the mounting board 100 with one side surface 2d of a pair of side surfaces 2c and 2d serving as a mounting surface MF. The external electrode 4 is electrically connected to the conductor layer 102, and the external electrode 5 is electrically connected to the conductor layer 102. The external electrodes 4 and the conductor layers 102 are fixed by solder 106. The external electrodes 5 and the conductor layers 103 are fixed by solder 107. The laminated coil component 1 is mounted on a mounting board 100 in a state in which the coil axis L extends along the surface of the board 101.

[0030] Next, the configuration of the conductor pattern 21 forming the coil pattern 12 will be described in detail with reference to Fig. 4(a). As shown in Fig. 4(a), the cross section of the element body 2 and the coil 10 have a rectangular shape with the Z-axis direction as the longitudinal direction and the X-axis direction as the short side direction. The coil 10 includes a pair of coil conductors 31, 32 extending in the X-axis direction, which is the short side direction, and a pair of coil conductors 33, 34 extending in the Z-axis direction, which is the long side direction. The cross-sectional shapes of the element body 2 and the coil 10 are not particularly limited, and may be rectangular or square with the X-axis direction as the longitudinal direction and the Z-axis direction as the short side direction.

[0031] The coil conductors 31 and 32 are spaced apart from each other in the Z-axis direction, with the coil conductor 31 disposed on the positive side of the Z-axis direction and the coil conductor 32 disposed on the negative side of the Z-axis direction. The coil conductor 31 is disposed at a position spaced apart from the side surface 2c on the negative side in the Z-axis direction. The coil conductor 32 is disposed at a position spaced apart from the side surface 2d on the positive side in the Z-axis direction. The coil conductors 33 and 34 are spaced apart from each other in the X-axis direction, with the coil conductor 33 disposed on the positive side in the X-axis direction and the coil conductor 34 disposed on the negative side in the X-axis direction. The coil conductor 33 is disposed at a position spaced apart from the side surface 2e on the negative side in the X-axis direction. The coil conductor 34 is disposed at a position spaced apart from the side surface 2f on the positive side in the X-axis direction.

[0032] The positive and negative ends of the coil conductor 33 in the Z-axis direction are connected to the positive ends of the coil conductors 31 and 32 in the X-axis direction. The positive and negative ends of the coil conductor 34 in the Z-axis direction are connected to the negative ends of the coil conductors 31 and 32 in the X-axis direction. As a result, the coil conductors 31, 32, 33, and 34 form a rectangular ring shape when viewed from the Y-axis direction. The coil pattern 12 shown in FIG. 4(a) has coil conductors 32, 33, and 34, and is open on the positive side in the Z-axis direction. The dimensional relationships described below are also applicable to coil patterns other than the coil pattern 12 shown in FIG. 4(a).

[0033] Next, the dimensional relationship of the laminated coil component 1 will be described. The size of the gap in the Z-axis direction between the coil 10 and the mounting surface MF in the cross section seen from the Y-axis direction is defined as a first gap G1. The size of the gap in the X-axis direction between the coil 10 and the side surfaces 2e and 2f in the cross section seen from the Y-axis direction is defined as a second gap G2. The size of the first gap G1 is the dimension in the Z-axis direction between the edge of the coil conductor 32 on the negative side in the Z-axis direction and the side surface 2d. The size of the second gap G2 is the dimension in the X-axis direction between the edge of the coil conductor 33 on the positive side in the X-axis direction and the side surface 2e. Alternatively, the size of the second gap G2 is the dimension in the X-axis direction between the edge of the coil conductor 34 on the negative side in the X-axis direction and the side surface 2f. Note that the second gap G2 on the coil conductor 33 side and the second gap G2 on the coil conductor 34 side may not be the same, and may be different from each other. In this case, the average value of the second gap on the coil conductor 33 side and the second gap on the coil conductor 34 side is adopted as the second gap G2. When the dimension in the Z-axis direction between the edge portion on the positive side in the Z-axis direction of the coil conductor 31 and the side surface 2c is defined as the third gap G3, the third gap G3 may have the same dimension as the first gap G1. However, the third gap G3 may have a dimension different from that of the first gap G1. The third gap G3 may have dimensional conditions similar to those of the first gap G1 described below. However, the dimensional relationship of the third gap G3 is not particularly limited, and it does not have to have the dimensional conditions of the first gap G1.

[0034] In a cross section seen from the Y-axis direction, the first gap G1 in the Z-axis direction between the coil 10 and the mounting surface MF is larger than the second gap G2 in the X-axis direction between the coil 10 and the side surfaces 2e, 2f. Specifically, the first gap G1 with respect to the second gap G2 may be 1.2 times or more, or 1.8 times or more. This allows a distance to be secured between the mounting surface MF of the element body 2 that is distorted by stress and the coil 10 to suppress cracks. The first gap G1 with respect to the second gap G2 may be 6.0 times or less, or 3.0 times or less. This allows the deterioration of inductance characteristics due to a reduction in the coil inner diameter to be suppressed. If the upper limit is exceeded, the coil inner diameter may be reduced, which may lead to a deterioration in inductance characteristics.

[0035] In a cross section seen from the Y-axis direction, the ratio of the first gap G1 to the dimension L1, which is the size of the element body 2 in the Z-axis direction, may be 12% or more, and may be 18% or more. This ensures a distance to suppress cracks between the mounting surface MF of the element body 2, which is distorted by stress, and the coil 10. Also, in a cross section seen from the Y-axis direction, the ratio of the first gap G1 to the dimension L1, which is the size of the element body 2 in the Z-axis direction, may be 30% or less, and may be 25% or less. This makes it possible to suppress a deterioration in inductance characteristics due to a reduction in the coil inner diameter. If the upper limit is exceeded, the coil inner diameter will be reduced, which may lead to a deterioration in inductance characteristics.

[0036] FIG. 5 is an enlarged cross-sectional view of the vicinity of the mounting surface MF as viewed from the Y-axis direction. As shown in FIG. 5, in the first region E1 between the mounting surface MF and the coil 10 in the element body 2, a surface region EA constituting the mounting surface MF and an internal region EB on the inside of the surface region EA are formed. The surface region EA is a region having a predetermined thickness from the side surface 2d toward the positive side in the Z-axis direction. The internal region EB is a region on the positive side of the surface region EA in the Z-axis direction. The surface region EA and the internal region EB may be formed in substantially the entire area of ​​the element body 2 in the Y-axis direction. The surface region EA is a region having a larger average crystal grain size than the internal region EB. Such a surface region EA is formed by increasing the sinterability of the surface region EA compared to the internal region EB. The ratio of the average crystal grain size of the surface region EA to the average crystal grain size of the internal region EB may be in the range of 1.2 to 2.0. The average crystal grain size of the surface region EA is not particularly limited, but may be set to 0.5 to 3.0 μm. The thickness of the surface region EA is not particularly limited, but may be set to 2 to 8 μm.

[0037] The surface region EA may be 2% or more of the first region E1, and may be 3% or more. In this case, the surface region EA can ensure a thickness for suppressing the occurrence of cracks. The surface region EA may be 25% or less of the first region E1, and may be 20% or less. The ratio of the surface region EA to the first region E1 may be the average value of the ratio of the thickness of the surface region EA to the thickness of the first region E1 in the Z-axis direction at each position in the X-axis direction. In this case, the thickness of the internal region EB sufficient to suppress the progression of cracks can be ensured. The second region E2 between the side surface 2c of the element body 2 and the coil 10, the third region E3 between the side surface 2e of the element body 2 and the coil 10, and the 43rd region E4 between the side surface 2f of the element body 2 and the coil 10 may have a layer structure similar to that of the first region E1.

[0038] Next, the functions and effects of the laminated coil component 1 according to this embodiment will be described.

[0039] This laminated coil component 1 is disposed inside an element body 2 and includes a coil 10 whose coil axis L extends in the Y-axis direction perpendicular to the Z-axis direction and the X-axis direction. One of a pair of side surfaces 2c, 2d facing each other in the Z-axis direction, that is, the side surface 2d, is a mounting surface MF. Therefore, the laminated coil component 1 is mounted in such a manner that the coil axis L extends along the surface of a mounting substrate 100 (see FIG. 3). At this time, stress is applied to the mounting surface MF of the laminated coil component 1 due to the effects of expansion and contraction of the conductor layers 102, 103 of the mounting substrate 100, etc.

[0040] Here, a laminated coil component 200 according to a comparative example will be described with reference to FIG. 4(b) and FIG. 6. As shown in FIG. 4(b), in the laminated coil component 200, the first gap G1 is equal to the second gap G2. Also, the ratio of the first gap G1 to the dimension L1 of the element body 2 is less than 12%. Next, with reference to FIG. 6, the principle by which cracks may occur when mounting the laminated coil component will be described. First, as shown in FIG. 6(a), cream solder 108 is applied onto the conductor layers 102 and 103 of the mounting board 100. Then, the laminated coil component 200 is mounted on the conductor layers 102 and 103 via the cream solder 108. Next, as shown in FIG. 6(b), when solder reflow mounting is performed, the conductor layers 102 and 103 of the mounting board 100 expand in a high-temperature reflow furnace. The conductor layers 102 and 103 expand to approach the center position of the element body 2. Next, as shown in FIG. 6(c), when the reflow is completed and the temperature drops, the conductor layers 102, 103 contract so as to move away from the center position of the element body 2. The contraction stress of the conductor layers 102, 103 is applied so as to horizontally stretch the mounting surface MF of the laminated coil component 1 mounted via the solders 106, 107. At this time, if the strength of the element body 2 is insufficient, a crack CR1 is generated in the vertical direction. In addition, a crack CR2 is formed from the end of the wraparound portion of the external electrodes 4, 5 on the mounting surface MF side to the vicinity of the corner of the element body 2, reaching the coil 10. The mounting procedure as shown in FIG. 6 is also applied to the laminated coil component 1 according to this embodiment.

[0041] In contrast, in a cross section viewed from the Y-axis direction, the ratio of the first gap G1 in the Z-axis direction between the coil 10 and the mounting surface MF to the size of the element body 2 in the Z-axis direction is 12 to 30%. In this case, a distance can be secured between the mounting surface MF of the element body 2, which is susceptible to distortion due to stress, and the coil 10, to prevent cracks. As a result, cracks due to stress during mounting can be prevented.

[0042] In a cross section viewed from the Y-axis direction, the first gap G1 may be larger than the second gap G2 in the X-axis direction between the coil 10 and the side surfaces 2e, 2f. In this case, a distance for suppressing cracks can be secured between the mounting surface MF of the element body 2, which is easily distorted by stress, and the coil 10.

[0043] The first gap G1 may be 1.2 to 6.0 times the second gap G2. In this case, a distance sufficient to prevent cracks can be secured between the mounting surface MF of the element body 2, which is susceptible to distortion due to stress, and the coil 10.

[0044] Here, the effect of suppressing cracks by increasing the first gap G1 will be described in more detail. As shown in FIG. 3, among the insulating material portions on the outer periphery side of the coil 10, the region DE1 having the mounting surface MF (shown in gray in FIG. 3) is a region that is easily distorted by stress due to expansion and contraction of the conductor layers 102 and 103. Since the distance of the region DE1 in the Z-axis direction is large, the stress acting per unit volume in the region DE1 is reduced. This suppresses the occurrence of cracks CR1 and CR2 (see FIG. 6(c)). Even if a crack CR2 occurs at a corner, the coil pattern 12 of the coil 10 is far away from the mounting surface MF, so that it is possible to suppress the crack CR2 from reaching the coil pattern 12 and causing a break in the wire. It is also possible to suppress the crack CR2 from blocking the magnetic flux B generated in the coil 10.

[0045] FIG. 8 shows the results of an experiment to confirm the effect of increasing the first gap G1. In this experiment, the dimensions L1=275 μm, L2=185 μm, L3=360 μm, and the gap G2=15 μm. Six types of laminated coil components with different first gaps G1 were prepared. 100 pieces of each type were prepared and mounted on a mounting board, and those in which a crack CR1 (see FIG. 6(c)) extending in the vertical direction was observed were considered to be "crack occurrence", and the ratio was calculated. A graph of the calculation results is shown in FIG. 8. The vertical axis of FIG. 8 is the crack occurrence rate, which is the ratio of the number of pieces in which a crack occurred out of 100 pieces. The horizontal axis is the ratio of the gap G1 to the dimension L1. As shown in FIG. 8, by setting the ratio of the gap G1 to the dimension L1 to 12% or more, it was confirmed that the crack occurrence suppression effect could be confirmed. The plot of the ratio of "G1 / L1=9%", that is, the leftmost plot in the graph, is the conventional structure according to the comparative example. It was confirmed that when the ratio was 12% or more, the crack occurrence rate (risk of crack occurrence) could be reduced to approximately half compared to the comparative example.

[0046] In the first region E1 between the mounting surface MF and the coil 10 in the element body 2, a surface region EA constituting the mounting surface MF and an internal region EB located inside the surface region EA are formed, and the surface region EA may have a larger average crystal grain size than the internal region EB. In this case, the surface region EA having a larger average crystal grain size can suppress the occurrence of cracks on the mounting surface MF. On the other hand, even if a crack occurs on the mounting surface MF, the internal region EB having a smaller average crystal grain size and pores can suppress the progression of the crack inward.

[0047] The surface region EA may be 2 to 25% of the first region E1. In this case, the effect of suppressing the occurrence of cracks on the mounting surface MF in the surface region EA and the effect of suppressing the progress of cracks in the internal region EB can be obtained in a well-balanced manner. FIGS. 7(a) and 7(b) show enlarged photographs near the surface region EA. As shown in FIG. 7(b), the surface region EA, which is the starting point of the cracks CR, has a small number of pores BA, so that the strength is high and cracks CR are unlikely to occur. Even if a crack CR occurs, since there are many pores BA in the internal region EB, the crack CR does not proceed straight toward the inside, but extends in a random direction between the pores BA. Therefore, the progress of the crack CR is suppressed in the internal region EB.

[0048] The present invention is not limited to the above-described embodiments.

[0049] For example, the configuration shown in FIG. 9 may be adopted. As shown in FIG. 9, the element body 2 may have a buffer section 50 with high cushioning properties on both sides in the Y-axis direction. The buffer section 50 is provided in the element body 2 at the locations having the end faces 2a and 2b. The buffer section 50 has a structure with a low Young's modulus. The standard section sandwiched between the pair of buffer sections 50 is a section in which the Young's modulus is set to the value of the standard element body 2, and has a higher Young's modulus than the buffer section 50. The size of the buffer section 50 is not particularly limited, and the buffer section 50 may extend to the coil 10 as shown in FIG. 9(a), or may be formed in a range that does not extend to the coil 10 as shown in FIG. 9(b). [Explanation of symbols]

[0050] 1...multilayer coil component, 2...element body, 2c, 2d...side surface (first side surface), 2e, 2f...side surface (second side surface), 10...coil, E1...first region, EA...surface region, EB...internal region, G1...first gap, G2...second gap, MF...mounting surface, L...central axis.

Claims

1. an element body having a pair of first side surfaces opposed to each other in a first direction and a pair of second side surfaces opposed to each other in a second direction perpendicular to the first direction; a coil disposed inside the element body and having a coil axis extending in a third direction perpendicular to the first direction and the second direction, One of the pair of first side surfaces is a mounting surface, a ratio of a first gap in the first direction between the coil and the mounting surface to a size of the body in the first direction in a cross section viewed from the third direction is 12 to 30%.

2. 2. The laminated coil component according to claim 1, wherein in a cross section viewed from the third direction, the first gap is larger than a second gap in the second direction between the coil and the second side surface.

3. 3. The laminated coil component according to claim 2, wherein the first gap is 1.2 to 6.0 times the second gap.

4. a surface region constituting the mounting surface and an internal region located inside the surface region are formed in a first region between the mounting surface and the coil in the element body, The laminated coil component according to claim 1 , wherein the surface region has a larger average crystal grain size than the inner region.

5. 5. The laminated coil component according to claim 4, wherein the surface region occupies 2 to 25% of the first region.

6. an element body having a pair of first side surfaces opposed to each other in a first direction and a pair of second side surfaces opposed to each other in a second direction perpendicular to the first direction; a coil disposed inside the element body and having a coil axis extending in a third direction perpendicular to the first direction and the second direction, One of the pair of first side surfaces is a mounting surface, a first gap in the first direction between the coil and the mounting surface is larger than a second gap in the second direction between the coil and the second side surface in a cross section viewed from the third direction.

7. 7. The laminated coil component according to claim 6, wherein the first gap is 1.2 to 6.0 times the second gap.

Citation Information

Patent Citations

  • Electronic component

    JP2012060049A